Designing Android Software Applying Augmented Reality on the Teaching and Studying of Gasoline Engine Sensors - Nguyen Tan, Ngoc (Journal of Technical Education Science, 2022)
Nowadays, the gasoline engine is still the heart of transportation in Vietnam. The total number of internal combustion vehicle in Vietnam is over 4 million, which is approximately 2.4 million petrol vehicles. The need of knowledge in the vehicle, especially the gasoline engine control system, is vital for maintenance and diagnostic process in this field. This paper is an introduction for applying the augmented reality and smartphone in teaching and studying input signals of the engine control system of gasoline engine in the Vehicle and Energy Faculty, HCMC University of Technology and Education, focusing on sensors. Augmented Reality (AR) is a new way of information sharing and interaction in mobile device (smartphone, tablet, etc.). AR in education brings truly realistic for teaching and learning process. Additional reality provides the unique cognition path with immersive real-life simulations, which help student accesses resources as real and freely as possible especially in the COVID-19 pandemic.